Combined deletion of PR-domain containing 16 (Prdm16) in cardiomyocyte and non-cardiomyocyte lineages results in spontaneous early-onset lethality and progressive left ventricular dysfunction in mice. (14th October 2021) - Van Wauwe, J; Craps, S; Zwijsen, A; Beerens, M; Luttun, A
Abstract: Introduction: PR-domain containing 16 (Prdm16) has an asymmetric expression pattern in the developing cardiovascular system, including ventricular myocardium, endocardium and arterial endothelial and smooth muscle cell (SMC) layers. Heterozygous PRDM16 mutations in humans have been linked with early-onset cardiomyopathy resulting in heart failure. Myocardial PRDM16-deficiency has been suggested as the culprit for this cardiomyopathy, however embryonic Prdm16 deletion in cardiomyocytes or their progenitors in mice only results in symptomatic cardiac defects upon metabolic stress or ageing. This suggests that Prdm16 loss in other cell types has an important co-contribution in the early heart phenotype seen in patients with causal PRDM16 variants. Purpose: To investigate the adjuvant role of non-cardiomyocytes to the heart phenotype caused by Prdm16 deficiency, we used a conditional mouse model in which deletion of Prdm16 occurs in all cells expressing an Sm22-driven Cre recombinase which has a combined activity in cardiomyocyte and non-cardiomyocyte lineages in the heart, including SMCs and pericytes. Methods: Mice carrying two Prdm16 alleles with a floxed exon 9 (Prdm16fl/fl) were intercrossed with the Sm22-Cre driver line. Offspring of Sm22Cre+; Prdm16fl/fl and Sm22Cre−; Prdm16fl/fl breeding pairs was monitored for Mendelian inheritance and for signs of (progressive) cardiac dysfunction by echocardiography at 5 and 16 weeks of age. Hearts were isolated and analyzed for RNA expression levels of cardiac stress markers Atrial and Brain Natriuretic Peptide (ANP and BNP) via quantitative RT-PCR and histologically for the appearance of fibrosis through Sirius red-staining. Results: Genotyping at 5 weeks of age showed a loss of 60.4% of Sm22Cre+; Prdm16fl/fl offspring. Mice surviving at 5 weeks spontaneously developed signs of left ventricular diastolic and systolic dysfunction, the latter shown by a significantly reduced ejection fraction (EF; 37±3% vs. 61±3% in control Sm22Cre−; Prdm16fl/fl littermates). Cardiac expression levels of ANP and BNP were significantly increased (728-fold and 36-fold, respectively) in Sm22Cre+; Prdm16fl/fl mice which also showed perivascular fibrosis compared to control littermates. At 16 weeks of age, this aberrant cardiac phenotype further progressed (EF: 32±3% vs. 57±4%; ANP: 2, 541-fold increase; BNP: 129-fold increase) and in addition to perivascular fibrosis, hearts also showed interstitial fibrosis (Sirius red+ area: 17±2% vs. 3.0±0.4% in control littermates). Conclusion: Unlike recently reported mice with a Prdm16 deficiency in cardiomyocytes or their (precursor) lineages, mice with a combined loss of Prdm16 in the cardiomyocytes and certain non-cardiomyocyte lineages feature early mortality and (progressive) signs of severe heart failure. Therefore, Prdm16 expressed by non-cardiomyocytes is indispensable for proper cardiac function and its loss in these cell types co-determines the aberrant cardiac phenotype. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Fonds voor Wetenschappelijk Onderzoek Strategic Basic Research pre-doctoral fellowship (1S25817N)KU Leuven Research Coordination grant (C14/19/095)